ABA Represses the Expression of Cell Cycle Genes and May Modulate the Development of Endodormancy in Grapevine Buds - Vergara, Ricardo; Noriega, Ximena; Aravena, Karla; Prieto, Humberto; Pérez, Francisco J. (Frontiers in Plant Science, 2017)
Recently, the plant hormone abscisic acid has been involved as key player in the regulation of endodormancy in grapevine buds (Vitis vinifera L). In this study, we show that in the vine, the expression of genes related to the biosynthesis of ABA (VvNCED1; VvNCED2) and the content of ABA are significantly higher at the latent bud than at the shoot-apex, while the expression of ABA catabolic gene (VvA8H3) showed no significant differences between both organs. A negative correlation between the content of ABA and transcript levels of the cell cycle genes (CCG) was found in both tissues. This result, suggested that ABA may regulate negatively the expression of the CCG in meristematic tissues of grapevines. To test this proposition, the effect of ABA on the expression of the CCG was analyzed in two meristematic tissues of the vine, somatic embryos and shoot-apex. The results indicated that cell-cycle progression is repressed by ABA in both organs, since it down-regulated the expression of genes encoding for cyclin-dependent kinases (VvCDKB1, VvCDKB2), for genes encoding cyclins type A (VvCYCA1, VvCYCA2, VvCYCA3), B (VvCYCB) and D (VvCYCD3.2a), and up-regulated the expression of VvICK5, a gene encoding for an inhibitor of CDKs. During the endodormancy the content of ABA increased and the expression of the CCG decreased. Moreover, the dormancy-breaking compound hydrogen cyanamide (HC) reduced the content of ABA and up-regulated the expression of the CCG. Taken together, these results suggest that ABA by repressing the transcription of the CCG may modulate the development of endodormancy in grapevine buds.